Assembly of a 9 ton cold storage facility at Masian Grup and Ping Loka Building Sleman Regency Yogyakarta - Hermawan, Ade; Syarifudin, Achmad; Sukismo, Hendro; Basino, Basino; Dewi, Priyantini; Extrada, Feby Riyan (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2023)
This study examines the assembly process of cold storage for frozen food business with a capacity of 9 tons. The aim of this research is to design and assemble a cold storage with dimensions of 5 m in length, 2.7 m in width, and 2.7 m in height, capable of storing frozen food products at a temperature of -18°C. The components used for the cold storage machine include a semi-hermetic Bitzer compressor, a fin and tube HD type condenser, and a wongso evaporator. The total cost for purchasing materials and assembly services for the cold storage amounts to Rp 164,776,980, including an 11% value-added tax (VAT).